Wooden residential buildings in the Kielce Region - Skoczylas, Olga (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The article summarized the characteristics features of cottages are the most frequently and less frequently in the region of Kielce. In article were specified the area to be taken into consideration in the article. Were collected basic types of division of Polish cottages and chosen this classification, which allows to use it to the needs of this publication. Then, based on the literature and photographs were selected representative features of each type.